PENGARUH PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN DI TELKOMSEL REGIONAL JAWA BARAT - Rosyidawaty, Soffi (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Career development is implemented because Telkomsel's target presented by President Commissioner Mr. Alex J Sinaga in 2017 will optimize the first Long Term Evolution (LTE) broadband technology in Indonesia so Telkomsel employees are prepared for long-term career, so that the company can also know career interest employees in the future through career development programs so that employees can produce better performance improvements that will be tailored to the level of education, knowledge, skills, employment, and employee performance appropriately and in accordance with the competencies and job qualifications required.The purpose of this study is to find out how good the career development is and to know how significant the influence of career development on employee performance at Telkomsel Regional Jawa Barat.